2019
DOI: 10.1177/0363546518820302
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Slope and Its Effect on Force in Anterior Cruciate Ligament Grafts: Anterior Cruciate Ligament Force Increases Linearly as Posterior Tibial Slope Increases

Abstract: Background: Previous work has reported that increased tibial slope is directly correlated with increased anterior tibial translation, possibly predisposing patients to higher rates of anterior cruciate ligament (ACL) tears and causing higher rates of ACL graft failures over the long term. However, the effect of changes in sagittal plane tibial slope on ACL reconstruction (ACLR) graft force has not been well defined. Purpose/Hypothesis: The purpose of this study was to quantify the effect of changes in sagittal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
170
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(181 citation statements)
references
References 25 publications
6
170
1
4
Order By: Relevance
“…Many studies, including this one, have confirmed that the steeper the tibial slope, the greater the risk of ACL injury, and some studies have calculated the threshold [14,18,19]. In this study, we found that the HAPR has better diagnostic and predictive value than the PTS.…”
Section: Discussionsupporting
confidence: 61%
“…Many studies, including this one, have confirmed that the steeper the tibial slope, the greater the risk of ACL injury, and some studies have calculated the threshold [14,18,19]. In this study, we found that the HAPR has better diagnostic and predictive value than the PTS.…”
Section: Discussionsupporting
confidence: 61%
“…3 This same study reported only 1 case of a postoperative ACL tear; however, such a large increase in posterior tibial slope compared with normal ranges increases the risk of future ACL tears and must be considered when surgically correcting genu recurvatum using a tibial osteotomy. 3,12,34 The reviewed studies that entailed osteotomies reported similar degrees of preoperative genu recurvatum in patients treated using either PTO alone or the Ilizarov method. Both corrective techniques also demonstrated similar subjective postoperative outcomes.…”
Section: Discussionmentioning
confidence: 93%
“… 33 Although this study reported improved subjective outcome scores according to the Hospital for Special Surgery scoring system (mean, 90.3 ± 9.0) and a high rate (83%) of patient satisfaction, such a significant degree of postoperative tibial slope may increase the risk of ACL instability at later follow-up. 3 This same study reported only 1 case of a postoperative ACL tear; however, such a large increase in posterior tibial slope compared with normal ranges increases the risk of future ACL tears and must be considered when surgically correcting genu recurvatum using a tibial osteotomy. 3 , 12 , 34 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Outros pesquisadores conseguiram provar que há aumento nas forças atuantes no LCA porém sua intensidade é muito pequena (BERNHARDSON et al, 2019;MAROUANE et al, 2014b). Neste último trabalho houve um acréscimo de cerca de 30 Newtons (N), durante a aplicação de uma força de compressão axial de 200 N, em um planalto com 20 graus de "slope".…”
Section: Método De Medição Do "Slope" Tibialunclassified